Aspirin and omega-3 fatty acid status interact in the prevention of cardiovascular diseases in Framingham Heart Study. (June 2021) - Block, Robert C.; Shearer, Gregory C.; Holub, Ashley; Tu, Xin M.; Mousa, Shaker; Brenna, J. Thomas; Harris, William S.; Tintle, Nathan
Highlights: Aspirin's cardiovascular effects in the Framingham Study differ by plasma levels of EPA and DHA. Events in those not taking aspirin with EPA and DHA in the second lowest quintile were reduced. Events in those taking aspirin with EPA and DHA in the second lowest quintile were increased. A personalized approach to both aspirin use and omega-3 supplementation may be needed. Abstract: Background: The roles of omega-3 (n3) fatty acids [eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)] and low-dose aspirin in the primary prevention of ischemic cardiovascular disease (CVD) are controversial. Since omega-3 (n3) fatty acids and aspirin affect cyclooxygenase activity in platelets, there could be a clinically-relevant effect of aspirin combined with a particular n3 fatty acid level present in each individual. Methods: RBC EPA+DHA, arachidonic acid (AA) and docosapentaenoic acid (DPA) were measured in 2500 participants without known CVD in the Framingham Heart Study. We then tested for interactions with reported aspirin use (1004 reported use and 1494 did not) on CVD outcomes. The median follow-up was 7.2 years. Results: Having RBC EPA+DHA in the second quintile (4.2–4.9% of total fatty acids) was associated with significantly reduced risk for future CVD events (relative to the first quintile, <4.2%) in those who did not take aspirin (HR 0.54 (0.30, 0.98)), but in those reporting aspirin use, risk was significantly increased (HR 2.16 (1.19, 3.92)) in this quintile. This interaction remained significant when adjusting for confounders. Significant interactions were also present for coronary heart disease and stroke outcomes using the same quintiles. Similar findings were present for EPA and DHA alone but not for DPA and AA. Conclusions: There is a complex interaction between aspirin use and RBC EPA+DHA levels on CVD outcomes. This suggests that aspirin use may be beneficial in one omega-3 environment but harmful in another, implying that a personalized approach to both aspirin use and omega-3 supplementation may be needed.